How effective are macroprudential policy instruments? Evidence from Turkey - Mahmut Çelik; Ayla Oğus̜ (Economies, 2022)
This study provides an empirical analysis of the two macroprudential instruments, namely the reserve option mechanism and the interest rate corridor, employed by the Central Bank of the Republic of Turkey in the aftermath of the global financial crisis. A nine-variable structural vector autoregressive model for Turkey is estimated with Bayesian techniques utilising data from October 2010 to May 2018. A set of timing, zero and sign restrictions are imposed to identify the reserve requirement and the interest rate shocks through the bank lending channel. The results reveal that the new policy frame is efficient in curbing the volatility in the exchange rates and in improving the current account balance. While the reserve requirements seem to be more effective on the current account and partly on the exchange rate, the interest rate fares better in controlling the price level.
Keywords: 330; Bayesian vector autoregression; interest rate corridor; macroprudential policy; reserve option mechanism; reserve requirements